(3CQLhRI aj GdCfZGes - (3fUQ Gddg Hf eMeO GdYLej GdTGaYj, GdNdNGdj,J (B962 (3g` s
(3ChdgG (B:s
(3QGZHG ai MUQ CfhGY GdfZe s
(3BNQgG (B:s
(3aGJHY UMjM cdeG fbdJg aCYdi (B( (3aCYde (B) (3Yf GdKbGJ bdJg s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3cJH HNW bdjd GdfbWs
(3fSNI KGfjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3afhf LejdI (B509) s
Keywords: (3GdehSjbi hGdZfGAs